Spatial Planning and Urban Development Critical Perspectives - Palermo, Pier Carlo; Ponzini, Davide (Urban and Landscape Perspectives, 2010)
Urban planning is a complex field of knowledge and practice. Through the decades, theoretical debate has formed an eclectic set of possible perspectives, without finding, in our opinion, a coherent paradigmatic framework which can adequately guide the interpretation and action in urban planning. The hypothesis of this book is that the attempts of founding an autonomous planning theory are inadequate if they do not explore two interconnected fields: architecture and public policies.The book critically reviews a selected set of current practices and theoretical founding works of modern and contemporary urban planning by highlighting the continuous search for the epistemic legitimization of a large variety of experiences. The distinctive contribution of this book is a documented critique to the eclecticism and abstraction of the main international trends in current planning theory. The dialogic relationship with the traditions of architecture and public policy is proposed here in order to critically review planning theory and practice. The outcome is the proposal of a paradigmatic framework that, in the authors' opinion, can adequately guide reflections and actions. A pragmatic and interpretative heritage and the project-orientated approach are the basis of this new spatial planning paradigm. Pier Carlo Palermo is Dean of the School of Architecture and Society at the Politecnico di Milano, where he founded and directed the Department of Architecture and Planning. His m ain research interests concern the theory and history of urbanism, urban studies, spatial planning and policy design. He has worked as planning consultant on programmes of national and international interest (EU Programmes, Italian Ministries of Economics, Environment, and Infrastructure and other territorial institutions). He has published numerous books on these topics. His most recent publications include: Innovation in Planning. Italian Experiences, Actar, Barcelona, 2006; I Limiti del Possibile. Governo del Territorio e Qualità dello Sviluppo, Donzelli, Rome, 2009. Davide Ponzini received his PhD in Urban Planning from the Politecnico di Milano where he is currently Assistant Professor in Urban Planning. His research activity focuses on the role of cultural policies and contemporary architecture in urban transformation and local development, and more recently on issues of urban planning and policy tools. He was visiting scholar at Yale University, Johns Hopkins University and Columbia University. He is the author of Il Territorio dei Beni Culturali, Carocci, Rome, 2008, editor (with Mattias Legnér) of Cultural Quarters and Urban Transformation, Gotlandica Forlag, Visby, 2009, as well as author of several articles published in Italian and international scientific journals.